Disability adjusted life years among arsenicosis patients in an arsenic-affected area of southern Bangladesh - Laskar, MS; Gazi, EA; Basu, BK; Chowdhury, S; Ahmad, SA; Khan, MH (Mediscope, 2015)
Disability adjusted life years (DALY) is the sum of the present value of future years of lifetime lost through premature mortality, and the present value of years of future life-time adjusted for the average severity of any mental or physical disability caused by a disease or injury. As a method for estimating the global burden of disease, DALY was first introduced in the World Development Report in 1993 by the World Bank. The aim of this study was to estimate DALY among arsenicosis patients. DALY was calculated for 104 arsenicosis patients from an arsenic-affected rural area of southern Bangladesh using the estimated years they lived with disability (YLD). The mean (SD) of cumulative arsenic exposure level was 5.0 (3.2) mg/l-years. Among the patients, 64% reported reduction in working ability. The portion of the patients with disability for more than 50 years was as high as 58.7%. The mean (SD) of YLD and DALY was 54.0 (9.8) and 9.2 (1.5), respectively. A total of 5621 YLD equivalent to 961.7 DALY was lost due to arsenicosis (when life expectancy at birth according to Bangladesh Bureau of Statistics was applied, the YLD and DALY were 3899.2 and 868.9, respectively). There was significant relationship of YLD with education of the patients (p < 0.05). There was significant relationship between DALY and education of the patients (p < 0.05). There was also significant relationship between DALY and reduction in working ability of the patients (p < 0.05). The findings of the study justify for the policy makers to adopt adequate measures such as prevention, treatment and rehabilitation to alleviate the sufferings of the arsenicosis patients. Mediscope Vol. 2, No. 1: 2015, Pages 4-12